Eglises, identités non confessionnelles et islam en Allemagne - Sylvie Toscer-Angot (Amnis)
Since the 1980s, the nature of relations between politics and religion in Germany has undergone some profound changes. Today, Germany is confronted with two seemingly contradictory phenomenon: on one hand Germany claims to have non-religious identities in the public realm, while on the other there are increasing demands from communities that desire to obtain new rights as well as institutional recognition and greater visibility in public space. Several factors are behind this movement: one is the growing importance of the numbers of non-religious personsthat has accelerated as a result of the effects of reunification, individualization and diversification of beliefs and religious practices; the other is the presence of increasingly assertive Islam. In response to the questions raised by the diversity of faiths, beliefs or affiliations, public authorities are trying to find political and legal ways that may reconcile the requirements of protection of fundamental freedoms (the freedoms of conscience and religion), the principle of neutrality of the state, equal treatment of all religious communities in respect to their traditions and heritages. In a country with a federal structure, where religious matters are the responsibility of the Länder, the responses to political and religious disputes vary widely from state to state. They relativize the historically constituted church-state relations in Germany and show different ways of treating religious pluralism. By relying in particular on the analysis of debates on religious education in schools, this contribution aims to show the process of deconfessionalization in Germany and to study the influence of Christian Churches on the relationship between the State and Muslim communities.Religion, politics, Islam, churches, church-state relations, public space, Germany, Twentieth century, Twenty-first century